Representasi Sejarah Reformasi Dalam Novel Laut Bercerita Karya Leila S. Chudori Dan Relevansinya Dalam Pembelajaran Novel Sejarah di SMA/SMK - I Dewa Gede Fathur Try Githa; I Made Sujaya; I Kadek Adhi Dwipayana (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This research focuses on the representation of the history of reform in the novel Laut Bercerita by Leila S. Chudori and its relevance to learning historical novels in SMA/SMK. Theoretically, this research serves as a means of developing literary knowledge, especially regarding literature and historical literary perspectives, as well as practically providing an understanding to the public about the history of reform in a literary work. This research can also contribute to Indonesian language teachers at the SMA/SMK level, because it has relevance to historical novels so that they are worthy of being used as teaching materials. This study uses a type of qualitative research. The source of the data in this study was the novel Laut Bercerita by Leila S. Chudori. This data was collected using the literature study method, then the children were analyzed using a qualitative descriptive method. After being analyzed, the results of this study show that the novel Laut tells the story of Leila S. Chudori, there are historical representations of reform, including the kidnapping and torture of activists, the banning of literary works, the fall of the Suharto regime, the formation of the missing persons commission and the disappearance of marine figures. In addition, based on research results by looking at the syllabus for learning historical novels, the novel Laut Bercerita is suitable as teaching material in learning historical novels in SMA/SMK.